Characterization of methicillin-resistant coagulase-negative staphylococci in milk from cows with mastitis in Brazil - Silva, Nathalia C. C. [UNESP]; Guimaraes, Felipe F. [UNESP]; Manzi, Marcela de P. [UNESP]; Gomez-Sanz, Elena; Gomez, Paula; Araujo-Junior, Joao P. [UNESP]; Langoni, Hélio [UNESP]; Rall, Vera L. M. [UNESP]; Torres, Carmen (Springer, 2014)
Staphylococci are one of the most prevalent microorganisms in bovine mastitis. Staphylococcus spp. are widespread in the environment, and can infect animals and humans as opportunistic pathogens. The objective of this study was to determine the frequency of methicillin-resistance (MR) among coagulase-negative staphylococci (CoNS) previously obtained from milk of mastitic cows in Brazil and to characterize the antimicrobial resistance phenotype/genotype and the SCCmec type of MRCoNS isolates. Identification of MRCoNS was based on both biochemical and molecular methods. Susceptibility testing for eleven antimicrobials was performed by disk-diffusion agar. Antimicrobial resistance genes and SCCmec were investigated by specific PCRs. Twenty-six MRCoNS were detected (20 % of total CoNS), obtained from 24 animals, and were identified as follows: S. epidermidis (7 isolates), S. chromogenes (7), S. warneri (6), S. hyicus (5) and S. simulans (1). All MRCoNS isolates carried mecA while the mecC gene was not detected in any CoNS. The SCCmec IVa was demonstrated in nine MRCoNS, while the remaining 17 isolates harbored non-typeable SCCmec cassettes. In addition to oxacillin and cefoxitin resistance, MRCoNS showed resistance to tetracycline (n = 7), streptomycin (n = 6), tobramycin (n = 6), and gentamicin (n = 4), and harbored the genes tet(K) (n = 7), str (n = 3), ant(4') (n = 6) and aac(6')-aph(2aEuro(3)) (n = 4), respectively. In addition, seven strains showed intermediate resistance to clindamycin and two to streptomycin, of which two harboured the lnu(B) and lsa(E) genes and two the aad(E) gene, respectively. One isolate presented intermediate erythromycin and clindamycin resistance and harbored an erm(C) gene with an uncommon 89-bp deletion rendering a premature stop codon. MRCoNS can be implicated in mastitis of cows and they constitute a reservoir of resistance genes that can be transferred to other pathogenic bacteria.
Keywords: Staphylococcus; Coagulase negative; mecA; Antimicrobial resistance; Bovine mastitis